2013
DOI: 10.1007/s12529-013-9347-5
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Retention of Children in Behavioral Health Risk Factor Studies: REACH Strategies

Abstract: Using multiple REACH strategies is most promising for maximizing response rates and minimizing attrition of children in cross-sectional, longitudinal, and behavioral intervention studies in community settings such as schools, child care centers, and other youth-related organizations. Researchers can select the most suitable strategies based on their specific study design and requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 49 publications
3
93
0
1
Order By: Relevance
“…In future research, active travel to non-school destinations should receive more attention as this study showed that active travel to non-school destinations is more common in children than active travel to school (53% versus 37%), hence, it may have more potential to increase children's physical activity levels than active school travel. The low response rate and substantial missing data in this study shows the common challenge of recruiting and retaining children in behavioral studies (Schoeppe et al, 2013). More guidance is needed on successful recruitment and retention strategies applied in child populations (Schoeppe et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In future research, active travel to non-school destinations should receive more attention as this study showed that active travel to non-school destinations is more common in children than active travel to school (53% versus 37%), hence, it may have more potential to increase children's physical activity levels than active school travel. The low response rate and substantial missing data in this study shows the common challenge of recruiting and retaining children in behavioral studies (Schoeppe et al, 2013). More guidance is needed on successful recruitment and retention strategies applied in child populations (Schoeppe et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…The low response rate and substantial missing data in this study shows the common challenge of recruiting and retaining children in behavioral studies (Schoeppe et al, 2013). More guidance is needed on successful recruitment and retention strategies applied in child populations (Schoeppe et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…In the literature, the use of champions is considered a general best practice for enrollment and retention. 30 There are different types of champions, including administrative and community champions. 31 Administrative champions are individuals from within an organization who can advocate for a project, assist with acquiring resources, or foster project development in some way.…”
Section: Engage a MIX Of Study Championsmentioning
confidence: 99%
“…In addition to community champions, other people connected to participants, or even participants themselves, can act as champions-for example, by explaining the project to others or advocating for others' participation. 30 In the AoURP, RMCs most often find that provider champions are effective advocates.…”
Section: Engage a MIX Of Study Championsmentioning
confidence: 99%
“…1316 Many of these programs, however, have struggled to engage and retain minority youth, 1722 which may contribute to disparities in diabetes risk and outcomes. In attempt to more effectively reach high-risk individuals, tailored and adapted approaches have been recommended that modify content, language, mode of delivery, theoretical approach or other intervention components to improve engagement and outcomes.…”
Section: Contextmentioning
confidence: 99%